2001
DOI: 10.4049/jimmunol.167.9.5150
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Suppression of Matrix Metalloproteinase-9 Gene Expression by IFN-γ and IFN-β: Critical Role of STAT-1α

Abstract: Matrix metalloproteinases (MMPs) are a family of zinc-dependent endopeptidases that play crucial roles in proteolytic degradation of the extracellular matrix. Aberrant expression of the 92-kDa type IV collagenase (MMP-9) is implicated in the invasion and angiogenesis process of malignant tumors and in inflammatory diseases of the CNS. We investigated the effects of IFN-γ and IFN-β, cytokines used for treating some cancers and multiple sclerosis, on MMP-9 expression in human astroglioma and fibrosarcoma cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 61 publications
3
119
0
2
Order By: Relevance
“…To gain insight in these early circuits, we studied the expression and the activation of STAT-1, which is in an intracellular target of IL-12-induced biologic activities (19,20) and negatively regulates MMP9 transcription (83). In our experimental conditions, we observe that STAT-1 is expressed and tyrosine phosphorylated in stimulated PBMC and CD4 ϩ cells regardless of the presence of ECs but not in stimulated CD8 ϩ , corroborating the morphologic observations discussed above.…”
Section: Discussionsupporting
confidence: 83%
“…To gain insight in these early circuits, we studied the expression and the activation of STAT-1, which is in an intracellular target of IL-12-induced biologic activities (19,20) and negatively regulates MMP9 transcription (83). In our experimental conditions, we observe that STAT-1 is expressed and tyrosine phosphorylated in stimulated PBMC and CD4 ϩ cells regardless of the presence of ECs but not in stimulated CD8 ϩ , corroborating the morphologic observations discussed above.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to receptor-activated Smads, Smad7 binds stably to TGF-b receptors and interferes with ligandinduced phosphorylation of Smad2 and Smad3 (Hayashi et al, 1997; Nakao et al, 1997). It has been shown that IFN-g inhibits the TGF-b signaling pathway through the induction of Smad7 or competition between Smads and STAT1 for limited amounts of the shared cellular coactivators p300/CBP (Ghosh et al, 2001;Ma et al, 2001). In our experiments, IFN-g inhibited the effects of TGF-b-dependent GCTM-1 invasion (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Also, IFN was shown to be able to down-regulate C/EBPα IFN was shown to down-regulate the IL-1 gene in murine macrophages but it was unable to do so in Stat1 -/-animals (De Boer et al, 2001). Furthermore, IFN suppresses MMP-9 via Stat1 (Ma et al, 2001b) and this appears to be due to sequestration of CBP/p300 such that this coactivator is not available for transcription of the MMP-9 gene (Ma et al, 2005).…”
Section: Effect Of Ifn On Binding Of Stat1 and Stat3 In The Intact Numentioning
confidence: 99%